2016
DOI: 10.1128/iai.01165-15
|View full text |Cite
|
Sign up to set email alerts
|

Lysine 11 -Linked Polyubiquitination of the AnkB F-Box Effector of Legionella pneumophila

Abstract: The fate of the polyubiquitinated protein is determined by the lysine linkages involved in the polymerization of the ubiquitin monomers, which has seven lysine residues (K 6 , K 11 , K 27 , K 29 , K 33 , K 48 , and K 63 ). The translocated AnkB effector of the intravacuolar pathogen Legionella pneumophila is a bona fide F-box protein, which is localized to the cytosolic side of the Legionella-containing vacuole (LCV) and is essential for intravacuolar proliferation within macrophages and amoebae. The F-box dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 71 publications
1
22
0
Order By: Relevance
“…125 Another study showed that AnkB is also modified by Trim21-mediated K11-linked ubiquitination; however, this fails to change its stability. 126 LegU1 and LegAU13 are integrated into the host SCF E3 complex, with the former directly ubiquitinating BAT3, a host co-chaperone of Hsp70 that is implicated in ER stress modulation. 127 SidC and its paralog SdcA, identified in L. pneumophila, are capable of recruiting the ER-derived vesicles to build LCV.…”
Section: Shigella Flexnerimentioning
confidence: 99%
“…125 Another study showed that AnkB is also modified by Trim21-mediated K11-linked ubiquitination; however, this fails to change its stability. 126 LegU1 and LegAU13 are integrated into the host SCF E3 complex, with the former directly ubiquitinating BAT3, a host co-chaperone of Hsp70 that is implicated in ER stress modulation. 127 SidC and its paralog SdcA, identified in L. pneumophila, are capable of recruiting the ER-derived vesicles to build LCV.…”
Section: Shigella Flexnerimentioning
confidence: 99%
“…Of the 300 effector proteins L. pneumophila secretes within host cells, many are employed to override substrate selectivity of host SCF E3 complexes (Bruckert and Abu Kwaik, 2016;Quaile et al, 2015). Well-documented examples include LubX, a U-Box containing protein, and F-box proteins AnkB and LegU1.…”
mentioning
confidence: 99%
“…HEK293T cells were transfected with 3XFLAG-AnkH, BAP, and c-myc-LARP7 for 24 h and collected in lysis buffer, as described previously [177,254]. FLAG-tagged and myc-tagged proteins were immunoprecipitated by using anti-FLAG M2 magnetic beads (Sigma) or SureBeads Protein G Magnetic Beads (BioRad) crosslinked with anti-myc antibody (ProteinTech).…”
Section: In Vivo Co-immunoprecipitationmentioning
confidence: 99%
“…Legionella pneumophila strains were lysed using B-PER (Thermo Scientific) and heated at 99°C for 5 minutes in sample buffer. 1 X 10 6 bacteria were loaded per lane and separated by 10.4 to 15% SDS-PAGE (BioRad), and transferred onto a polyvinylidene difluoride (PVDF) (BioRad) membrane, as described previously [254] Immunoprecipitated proteins were heated at 99°C for 5 minutes in sample buffer, separated by 10.4 to 15% SDS-PAGE (BioRad), and transferred onto a polyvinylidene difluoride (PVDF) (BioRad) membrane, as described previously [254]. Anti-Flag Biologics and was used at a dilution of 1:100 [186,187].Cya-hybrids were detected using monoclonal M-45 antibody at a dilution of 1:50 [53].…”
Section: Antibodies and Western Blot Analysismentioning
confidence: 99%